2013
DOI: 10.1038/hdy.2013.95
|View full text |Cite
|
Sign up to set email alerts
|

Pollen flow in fragmented landscapes maintains genetic diversity following stand-replacing disturbance in a neotropical pioneer tree, Vochysia ferruginea Mart

Abstract: In forests with gap disturbance regimes, pioneer tree regeneration is typically abundant following stand-replacing disturbances, whether natural or anthropogenic. Differences in pioneer tree density linked to disturbance regime can influence pollinator behaviour and impact on mating patterns and genetic diversity of pioneer populations. Such mating pattern shifts can manifest as higher selfing rates and lower pollen diversity in old growth forest populations. In secondary forest, where more closely related pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 56 publications
(78 reference statements)
2
16
0
Order By: Relevance
“…Under these conditions, pollinator behavior is expected to be impacted by the great variation in tree density between old growth (low density) and secondary forest (high density). These assumptions are tested for the long-lived, self-compatible pioneer tree, Vochysia ferruginea, at old growth and secondary forest sites in Costa Rica (Davies et al, 2015). Progeny from both old growth and secondary forest contexts were predominantly outcrossed and experienced low levels of biparental inbreeding, indicating that the mating patterns of V. ferruginea are relatively robust to density differences between old growth and secondary forest stands.…”
Section: Overview Of the Focal Issue Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Under these conditions, pollinator behavior is expected to be impacted by the great variation in tree density between old growth (low density) and secondary forest (high density). These assumptions are tested for the long-lived, self-compatible pioneer tree, Vochysia ferruginea, at old growth and secondary forest sites in Costa Rica (Davies et al, 2015). Progeny from both old growth and secondary forest contexts were predominantly outcrossed and experienced low levels of biparental inbreeding, indicating that the mating patterns of V. ferruginea are relatively robust to density differences between old growth and secondary forest stands.…”
Section: Overview Of the Focal Issue Studiesmentioning
confidence: 99%
“…The second study asks whether some forest contexts are more sensitive than others to population genetic impacts (Davies et al, 2015). During the colonization of open landscapes, seed-source bottlenecks can cause a severe reduction in genetic diversity and is particularly an issue for secondary forest colonizing trees (Davies et al, 2010).…”
Section: Overview Of the Focal Issue Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Schleuning, Niggemann, Becker, and Matthies () concluded that the longevity of Trifolium montanum has likely delayed extirpation of some populations. A lag in fitness declines in perennial species may be particularly long if there is strong selection against selfed progeny (Davies et al., ; Delmas et al., ; Young, Boyle, & Brown, ). Strong selection against inbred progeny in T. virginicum is suspected as census size estimates for some populations in 1984 were exactly the same in 2013; however, we cannot eliminate other factors such as poor pollinator visitation rates or habitat degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its ability to grow in barren soils, high capacity to sprout, and tolerance to disturbance, Q. fabri is not only a pioneer species for secondary succession of evergreen broadleaved forests (EBLFs) but also plays an important role in the recovery of EBLFs, which have suffered from serious anthropogenic destructions in China and need to be restored and managed efficiently (Song and Chen, 2007). It is therefore necessary to identify the genetic variation of Q. fabri because a better understanding of the genetic background of early successional species will greatly contribute to the success of preliminary stages in forest recovery (Davies et al, 2015).…”
Section: Introductionmentioning
confidence: 99%